Implementation of Total Quality Management (TQM) and Malcolm Baldrige National Quality Award (MBNQA) for Work Quality Improvement - Lukmandono, Lukmandono; Syaiin, Moh Nur (Jurnal IPTEK, 2024)
Performance measurement is needed to improve organizational performance by systematically measuring the level of performance achievement. This is done so that the company can know its position so that improvements can be made which will have an impact on increasing the productivity of the company. PT Esa Solusi Mandiri with the brand name Esaco is a consulting, training, assessment and equipment inspection agency. Esaco needs to improve its performance because the success of a company can be assessed by accurate and precise performance indicators to reflect its competitiveness. The approach used for performance measurement uses the Malcolm Baldrige National Quality Award (MBNQA). This study shows that Esaco's performance is in the average category with a score of 416.17, which indicates that the company is in the early improvement stage in the service sector.